2022
DOI: 10.1371/journal.pone.0263229
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tourism competitiveness and mechanisms of spatial differentiation in Xinjiang, China

Abstract: Evaluation of tourism competitiveness is useful for measuring the level of regional tourism development. It is of great importance to understand the advantages and disadvantages of tourism development correctly and formulate corresponding development strategies. To investigate tourism competitiveness, this paper established an evaluation index system, including tourism development competitiveness, tourism resource competitiveness, and tourism-support competitiveness, for 14 prefectures and cities in Xinjiang i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Altay, Yili, and Urumqi City are particularly appealing to local and international visitors due to their unique natural landscapes and cultural heritage. The research identi es a clear resource monopoly within Xinjiang's tourism industry, consistent with the resource-centric phase that characterizes the region's tourism sector (Liu et al, 2022). According to recent research by Miao Xin…”
Section: Heterogeneity Analysis Of Tourism-economy-ecological Environ...supporting
confidence: 64%
“…Altay, Yili, and Urumqi City are particularly appealing to local and international visitors due to their unique natural landscapes and cultural heritage. The research identi es a clear resource monopoly within Xinjiang's tourism industry, consistent with the resource-centric phase that characterizes the region's tourism sector (Liu et al, 2022). According to recent research by Miao Xin…”
Section: Heterogeneity Analysis Of Tourism-economy-ecological Environ...supporting
confidence: 64%
“…Recently, special attention has been paid to the role of entropy in tourism markets (Gu et al, 2019;Ruiz Reina, 2021;Liu et al, 2022), especially since information entropy provides greater accuracy and superior objectivity, which leads to a more comprehensive interpretation of the results (Teixeira et al, 2021). Bearing that in mind, this paper applies the just mentioned concept of entropy to measure the equality of natural and cultural resources in the context of tourism competitiveness.…”
Section: Resultsmentioning
confidence: 99%
“…There are number of studies on tourism destination competiveness (TDC), which have identified range of indicators and variables. The major literature reviewed on indicators and variables for the current include Liu, 2022;WEF, 2022;Kunst, & Ivandić, 2021;Goffi, 2013;Dupeyras & Mac Callum, 2013;White et al, 2006;Dwyer & Kim, 2003;Ritchie & Crouch, 2003. However, these studies show that there is no a specific, standard group of indicators applicable to any destination and researchers has established different group of indicators and variables based on local physical and socio-cultural context as well as level of economic development, which are considered to be the most relevant features to achieve competitiveness (Dwyer & Kim, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…They have identified three major components of tourism competitiveness: i) primary resources and activities, which refer to core resources, attractors, and tourism services, ii) secondary resources and activities, which refer to infrastructure, destination management, and tourism planning and policies, and iii) tourist demand. Likewise, different methods to measure competitiveness are identified and two broad approaches applied are quantitative/deterministic and qualitative analysis based on different sets of indicators (Liu et al, 2022;Lopes et al, 2018;Cibinskiene & Snieskiene, 2015;Goffi, 2013;Enright & Newton, 2004;Ritchie & Crouch, 2003). This study is based on integrated approach by adopting tourism component of Ritchie and Crouch (2003) and selected tourism destination competitiveness indicators of Goffi (2013) as presented in Figure 1.…”
Section: Conceptual Frameworkmentioning
confidence: 99%